GROWTH AND SEED YIELD OF CARROT AS INFLUENCED BY DIFFERENT REGIMES OF NITROGEN AND POTASSIUM - Amjad, Muhammad; Naz, Safina; Ali, Sultan (Journal of Research (Science), 2025)
The research was conducted to observe the effect of different N and K levels on carrot growth and seed yield during 2002-2003. Different combinations of N and K levels had no significant effect on sprouting percentage, number of tertiary umbels and total number of umbels per plant, seed weight of primary, secondary and tertiary umbels. Plant height, number of secondary umbels perplant, seed yield of primary, secondary and tertiary umbels per hactare and total seed yield were affected by various combinations of N and K levels. A combination of 75 kg N and 90 kg K ha-1 was most effective for obtaining maximum seed yield ha-1